Fluktuasi Harga Dan Kesejahteraan Petani Tembakau Madura - Achmarul Fajar; Siti Maulidah (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2021)
Abstract— The growth of the cigarette industry does not necessarily improve the welfare of tobacco farmers Madura. Pamekasan as the largest tobacco center in Madura often experiences fluctuations of tobacco prices which have an impact on the economic uncertainty of tobacco farmers. The factors of fluctuating tobacco prices are the main topic of this research. This research on fluctuations of tobacco prices and the economy of Madura tobacco farmers used qualitative methods by searching for data directly in the field through semi-structured interviews. The result is that several factors have led to fluctuations of tobacco prices in the Pamekasan area. First, the factor of weather or climate change is uncertain. Second, the length of the tobacco distribution chain to the warehouses of major cigarette companies in Indonesia which are based in the Pamekasan area. Third, local regulation no. 4 of 2015 which is not consistently implemented so that tobacco farmers are not sovereign in determining the selling price of Madura tobacco. Keywords—: Fluctuations of Tobacco Prices; Madura Tobacco; The Economy of Madura Tobacco Farmers.